2014
DOI: 10.1248/bpb.b14-00535
|View full text |Cite
|
Sign up to set email alerts
|

Terpene-Containing PEGylated Liposomes as Transdermal Carriers of a Hydrophilic Compound

Abstract: We investigated the effect of PEGylated liposomes (PLs) containing a terpene on the penetration of a hydrophilic compound through porcine skin. PLs composed of N-(carbonyl-methoxypolyethyleneglycol-2000)-1,2-distearoyl-sn-glycero-3-phosphoethanolamine (PEG 2000 -DSPE), the sodium salt of PEG 2000 -DSPE, phosphatidylcholine (PC), cholesterol (Chol), Tween 20, and d-limonene were prepared as carriers for fluorescein sodium (NaFI). The physicochemical characteristics of PLs and their effects on in vitro skin pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…The polarity of the bilayer vesicles in the presence of PEGylated-lipids was more than that of the non-PEG modified liposomes. Thus, 15,20) For the niosome formulations, the %EE was 29 to 41%. The %EE of the niosomes was higher than that of the PEGylated niosomes (NIP1-4), suggesting that the PEG chain may make the niosome structure more rigid and decreased drug entrapment.…”
Section: Resultsmentioning
confidence: 99%
“…The polarity of the bilayer vesicles in the presence of PEGylated-lipids was more than that of the non-PEG modified liposomes. Thus, 15,20) For the niosome formulations, the %EE was 29 to 41%. The %EE of the niosomes was higher than that of the PEGylated niosomes (NIP1-4), suggesting that the PEG chain may make the niosome structure more rigid and decreased drug entrapment.…”
Section: Resultsmentioning
confidence: 99%
“…17 The drug entrapment efficiency of CL, PL, and PL-LI was 17.33%±1.13%, 21.76%±1.56%, and 29.60%±2.35%, respectively. According to the presence of PEG-lipids in the liposome formulation, the membrane bilayer became more polar and the efficiency of incorporation of the hydrophilic drug increased.…”
mentioning
confidence: 89%
“…16 In addition, our previous work reported that d-limonene containing PL provided a synergistic effect to enhance penetration of hydrophilic compounds into and through the skin. 17 Therefore, the aim of this study was to investigate the effect of low frequency SN (20 kHz) on the follicular pathway for transport of sodium fluorescein (NaFI)-loaded PL into porcine skin. PL containing d-limonene has been used as a carrier to enhance transdermal delivery of hydrophilic NaFI, with the transfollicular pathway as the major penetration pathway.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Os LCs são formados geralmente por fosfolipídios, com ou sem a adição de colesterol. Em 1992, CEVC e BLUME (1992) introduziram os lipossomas ultradeformáveis, usualmente chamados de Transfersomas® (IDEA AG, Munique, Alemanha).Lipossomas ultradeformáveis (UDL) são vesículas formadas por fosfolipídios e tensoativos, tais como surfactantes ou co-solventes que são capazes de enfraquecer as bicamadas lipídicas, diminuindo a tensão superficial, o que permite ao lipossoma mudar 23 a sua forma e, por conseguinte, levar a um aumento da deformabilidade das bicamadas que lhes permite por si só passar entre as células (ASCENSO et al, 2015) (Figura 9).Em virtude de sua natureza elástica e deformação, seu emprego como sistema de liberação transdérmica vem sendo recentemente estudado (CADDEO et al, 2015;LI et al, 2014c;RANGSIMAWONG et al, 2014;SAUVAGEOT et al, 2009;TYAGI et al, 2015). A eficácia dos UDLs tanto para sistemas de liberação dérmica e transdérmica tem mostrado resultados promissores encapsulando fármacos de diversos tamanhos moleculares e lipofilicidade diferentes, como por exemplo: lidocaína, tetracaína, hidrocortisona, dexametasona, o diclofenaco, o tamoxifeno, a testosterona (DUANGJIT et al, 2012;GHARIB et al, 2015;MAESTRELLI et al, 2010; SRISUK et al, 2012).…”
unclassified